Incidence of Colorectal Cancer in Loei Province, 2017-2022 - Dasaeng, Rungfa; Thipsanthiah, Kodchakorn; Kamsa-ard, Supot; Srisukhumchai, Nithi; Seehawong, Sabaiprae; Srimachan, Supanee; Kasamrothjanathanan, Narawadee (Srinagarind Medical Journal, 2024)
Background and Objective: Colorectal cancer (CRC) is ranks as the third most common cause of mortality globally for both gender. CRC, or colorectal cancer, is on the rise and has become a significant global public health concern. Currently, there is a lack of research regarding the incidence of CRC in Loei Province and the northeastern region of Thailand. The objective of this study was to ascertain the incidence of CRC in the Loei province from 2017 to 2022. Methods: A retrospective cohort study was undertaken utilizing data from the Loei population-based cancer registry (LPBCR) for the years 2017 to 2022. Estimation were made for both the crude rates and age-standardized rates, (ASR). The ASR, along with its corresponding 95% confidence interval, was then reported. Results: Out of a total of 754 patients with CRC, there were 465 cases of colon cancer and 289 cases of rectal cancer. The crude incidence rate for both gender was 23.5 per 100,000 person-years. The overall incidence of ASR was 13.7 per 100,000 person-years for both gender. The 95%CI: for the ASR for males was 15.5 per 100,000 person-years, with a range of 14.70 to 16.38. For females, the ASR was 12.1 per 100,000 person-years, with a range of 11.23 to 12.91. Conclusion: The incidence of colorectal cancer in Loei province was significantly high among both males and females. Additional investigation should prioritize the examination of temporal patterns in the incidence of CRC. This initiative aims to address the prevention and control of CRC both locally and nationally.